2018
DOI: 10.1016/j.cell.2018.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial One-Carbon Pathway Supports Cytosolic Folate Integrity in Cancer Cells

Abstract: SUMMARY Mammalian folate metabolism is comprised of cytosolic and mitochondrial pathways with nearly identical core reactions, yet the functional advantages of such an organization are not well understood. Using genome-editing and biochemical approaches, we find that ablating folate metabolism in the mitochondria of mammalian cell lines results in folate degradation in the cytosol. Mechanistically, we show that QDPR, an enzyme in tetrahydrobiopterin metabolism, moonlights to repair oxidative damage to tetrahyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 56 publications
3
78
0
Order By: Relevance
“…Transcripts for mitochondrial proteins involved in folate synthesis, MTHFD2L, MTHFD2, MTHFD1L and SHMT2 were all upregulated, whereas transcripts for the cytosolic part of the one-carbon cycle, DHFR, SHMT1, TYMS and MTHFD1 were downregulated in galactose. Mitochondrial folate metabolism is responsible to supply the cytosol with formate for purine synthesis, and for the synthesis of NADPH in mitochondria (Martinez-Reyes & Chandel, 2014, Zheng, Lin et al, 2018. The same tendency was observed comparing patient cells in glucose versus patient cells in galactose, indicating a marked shift in one carbon metabolism in patient cells in galactose in particular ( Fig.…”
Section: Rnaseq Analysis Reveals Reorganization Of One-carbon Metabolismsupporting
confidence: 55%
See 1 more Smart Citation
“…Transcripts for mitochondrial proteins involved in folate synthesis, MTHFD2L, MTHFD2, MTHFD1L and SHMT2 were all upregulated, whereas transcripts for the cytosolic part of the one-carbon cycle, DHFR, SHMT1, TYMS and MTHFD1 were downregulated in galactose. Mitochondrial folate metabolism is responsible to supply the cytosol with formate for purine synthesis, and for the synthesis of NADPH in mitochondria (Martinez-Reyes & Chandel, 2014, Zheng, Lin et al, 2018. The same tendency was observed comparing patient cells in glucose versus patient cells in galactose, indicating a marked shift in one carbon metabolism in patient cells in galactose in particular ( Fig.…”
Section: Rnaseq Analysis Reveals Reorganization Of One-carbon Metabolismsupporting
confidence: 55%
“…The upregulation of GOT1 in the patient cells likely indicates increased aspartate synthesis as an adaptation to the nutrient stress and to allow them to eventually proliferate. Also, an increase in mitochondrial folate metabolism could result from an increased need of formate in the cytosol, supplied by mitochondria for purine synthesis for growth (Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic analysis of 10,000 HSC/MPPs from the bone marrow of methotrexate-treated and control mice revealed that the only pathway that was significantly enriched among the metabolites that differed was "purine metabolism". While methotrexate would also be expected to alter folate metabolism, folate species are very difficult to detect by metabolomics (Zheng et al, 2018 and are not detected by our method. Given that methotrexate inhibits ATIC, AICAR levels would be expected to increase after methotrexate treatment (Cronstein et al, 1993, Baggott et al, 1986, Allegra et al, 1985.…”
Section: Metabolomic Profiling Of Hsc/mppsmentioning
confidence: 93%
“…Mitochondrial serine hydromethyltransferase (SHMT2) provides methyl groups for the synthesis of taurinomethyluridine, which in turn is required for efficient mitochondrial protein synthesis (Morscher et al, 2018). Mitochondrial formate production also contributes to maintain low levels of cytosolic tetrahydrofolate (Zheng et al, 2018). Tetrahydrofolate is prone to oxidative damage and breakdown leading to the formation of toxic products (Burgos-Barragan et al, 2017;Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial formate production also contributes to maintain low levels of cytosolic tetrahydrofolate (Zheng et al, 2018). Tetrahydrofolate is prone to oxidative damage and breakdown leading to the formation of toxic products (Burgos-Barragan et al, 2017;Zheng et al, 2018). In contrast other folate species such as 10-formyl-tetrahydrofolate are more stable.…”
Section: Introductionmentioning
confidence: 99%